2006
DOI: 10.1111/j.1469-8137.2006.01643.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione reductase from pea leaves: response to abiotic stress and characterization of the peroxisomal isozyme

Abstract: The glutathione reductase (GR; EC 1.6.4.2) isozyme present in peroxisomes has been purified for the first time, and its unequivocal localization in these organelles, by immunogold electron microscopy, is reported. The enzyme was purified c. 21-fold with a specific activity of 9523 units mg(-1) protein, and a yield of 44 microg protein kg(-1) leaves was obtained. The subunit size of the peroxisomal GR was 56 kDa and the isoelectric point was 5.4. The enzyme was recognized by a polyclonal antibody raised against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(47 citation statements)
references
References 60 publications
1
42
0
2
Order By: Relevance
“…Similar expression patterns were observed for OsGR1 in that expression was mainly observed in root and calli, rather than in leaves (Kaminaka et al 1998). Conversely, the expression of PsGR2 was very low in root tissue and weak in shoots and flowers (Stevens et al 1997;Romero-Puertas et al 2006). These results suggest that the expression of graminaceous and non-graminaceous GR may be regulated differently.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Similar expression patterns were observed for OsGR1 in that expression was mainly observed in root and calli, rather than in leaves (Kaminaka et al 1998). Conversely, the expression of PsGR2 was very low in root tissue and weak in shoots and flowers (Stevens et al 1997;Romero-Puertas et al 2006). These results suggest that the expression of graminaceous and non-graminaceous GR may be regulated differently.…”
Section: Discussionmentioning
confidence: 80%
“…These results suggest that the expression of graminaceous and non-graminaceous GR may be regulated differently. It has also been reported that the expression of PsGR1 and PsGR2 are regulated differentially in response to various stresses such as mechanical wounding and increased temperature (Romero-Puertas et al 2006). In barley, both HvGR1 and HvGR2 were upregulated by Fe-deficiency, whereas wheat exposed to the same conditions only exhibited increased levels of TaGR2 (Fig.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The higher proportion of humic-like substances and aromaticity in oak extracts than reed extracts suggest humic-like substances might trigger the upregulation of GR, which ultimately enhances the re-conversion of GSSG to GSH required for various ROS-scavenging and detoxification mechanisms during oxidative stress (Romero-Puertas et al, 2006). Humic materials have been shown to induce significant transcriptional changes in the stress-related biotransformation enzymes, GST and cytochrome P450 (Menzel et.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, peroxisomes also contain a battery of enzymes capable of detoxifying H 2 O 2 , catalase, and ascorbate peroxidase (APX) (Bunkelmann and Trelease 1996), an enzymatic component of the ascorbate-glutathione cycle, which is located in the peroxisomal membrane (Corpas and Trelease 1998). The peroxisomal NADP-ICDH is also essential for the ascorbate-glutathione cycle as it regenerates NADPH used by the GR and MDAR (Leterrier et al 2005;Romero-Puertas et al 2006). In other words, in the picdh-1 and picdh-2 mutants, the absence of a functional peroxisomal NADP-ICDH isozyme could prevent the efficient removal of H 2 O 2 (and consequently the H 2 O 2 -induced NO) by the peroxisomal ascorbate-glutathione cycle, leading to stomatal closure.…”
Section: Peroxisomal Nadp-icdh Is Necessary For Stomatal Openingmentioning
confidence: 99%